EPID-05. TREATMENT PATTERNS OF GLIOMAS: AN EPIDEMIOLOGICAL STUDY. (12th November 2021) - Bajwa, Mohammad Hamza; Imran, Noor; Shah, Mashal; Baig, Erum; Laghari, Altaf Ali; Bin-Anis, Saad; Akhunzada, Naveed Zaman; Gilani, Jaleed; Jawed, Noyan; Khalid, Usman; Qadeer, Namra; Lutfi, Areeb; et al.
Abstract: INTRODUCTION: Gliomas are the most common malignant brain tumors of the central nervous system in adults. Specialized treatment modalities have improved morbidity and mortality within high-income countries. In lower- and middle-income countries (LMICs), the overall mortality rate is still seen to be alarmingly high. As there is a shortage of statistical data available regarding the epidemiology of these tumors and their management within the country, the objective of this study is to define the landscape of treatment patterns and current epidemiological data regarding gliomas in Pakistan. METHODS: As part of the Pakistan Brain Tumor Epidemiology Study (PBTES), data was collected from major neurosurgical centers across the country, consisting of 35 hospitals in all 4 provinces. Our retrospective study looked at patients who underwent surgical procedures for gliomas in 2019, where a surgical pathology was available. The data was collated and analyzed using appropriate statistical methods. RESULTS: 791 patients with gliomas were identified (61.8 % in public sector hospitals, 39.1% in private sector). The most common histopathological subtypes were glioblastoma (33.5%), followed by astrocytoma (18.8%) and oligodendroglioma (11.9%). Gender distribution was skewed towards men (65%). The most commonly performed initial surgical procedure was gross total resection (50% in public hospitals, 41% in private hospitals). Private institution hospitals performed surgical biopsies as the first surgical procedure (23%) more often than public hospitals (9%). Regarding adjuvant treatments, only 26% of patients were given chemotherapy, and there was no data regarding 53% of patients. Similarly, only 15% of patients received radiation therapy, and there was no data for 60% of patients. CONCLUSIONS: Our study was able to identify the gaps in glioma management within Pakistan, particularly with regards to chemoradiotherapy. Identifying these unmet needs is the first step in developing comprehensive care for glioma patients.